The Impact of Corporate Governance and Firm Characteristics on Financial Performance of Listed Firms in Ghana - Anthony Ashun; Sagoe Abass Alhassan; Sani Abubakar; Evans Tetteh Akoto (Journal of Enterprise and Development (JED), 2026)
Purpose: This study investigates the impact of corporate governance mechanisms and firm-specific characteristics on financial performance among listed companies in Ghana.Method: The study employs panel data analysis of secondary data from 2013 to 2022 for firms listed on the Ghana Stock Exchange, utilizing key performance indicators (ROE, ROA, and GPM) and explanatory variables (board size, board independence, firm size, leverage, and firm age).Result: The findings indicate that board size has a significant positive relationship with both ROE and ROA, suggesting that larger boards enhance monitoring capacity and strategic oversight. However, board independence shows no significant effect on profitability, implying that the mere presence of independent directors may not lead to improved financial performance. Additionally, firm size and age are positively associated with profitability, emphasizing the importance of organizational maturity and scale in sustaining financial outcomes. Conversely, leverage negatively affects both ROA and GPM.Practical Implications for Economic Growth and Development: The study advocates for reforms that promote functional governance practices and cautions against the universal application of board composition norms. The findings have implications for policymakers, investors, and corporate boards aiming to optimize governance structures for financial resilience.Originality/Value: This study provides novel insights into the corporate governance-performance relationship in Ghana by utilizing advanced econometric techniques. It addresses a significant gap in the literature, particularly in the context of emerging markets, by analyzing a decade of firm-level data from Ghana's listed companies.